Advancements in mammalian cell transient gene expression (TGE) technology for accelerated production of biologics. (18th August 2018) - Gutiérrez-Granados, Sonia; Cervera, Laura; Kamen, Amine A.; Gòdia, Francesc
Abstract: Transient gene expression (TGE) in animal cell cultures has been used for almost 30 years to produce milligrams and grams of recombinant proteins, virus-like particles and viral vectors, mainly for research purposes. The need to increase the amount of product has led to a scale-up of TGE protocols. Moreover, product quality and process reproducibility are also of major importance, especially when TGE is employed for the preparation of clinical lots. This work gives an overview of the different technologies that are available for TGE and how they can be combined, depending on each application. Then, a critical assessment of the challenges of large-scale transient transfection follows, focusing on suspension cell cultures transfected with polyethylenimine (PEI), which is the most widely used methodology for transfection. Finally, emerging opportunities for transient transfection arising from gene therapy, personalized medicine and vaccine development are reviewed.